Application of Fuzzy Logic in Prediction to Determine the Value of Water Quality and Environment in Lettuce Hydroponics - Gusti Ramdani; Ahmadiki Firman Dwi Suryawan; Muhammad Raihan Ramadhan Steyer (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
The need for food such as vegetables and fruits will never stop. Meanwhile, with the times, agricultural land is decreasing. In order to meet food needs, the community needs to make efforts to utilize limited agricultural land by applying hydroponic farming techniques. With hydroponic techniques, people can produce vegetables and fruits to fulfill their food needs. Yields from hydroponics are influenced by several factors, such as water quality and the surrounding environment. In grouping the quality of crops can use the help of fuzzy logic. That way, the application of fuzzy logic in hydroponic farming techniques is useful for assessing the quality of food needs